Torture and textuality: Guantánamo Diary as postcolonial text. Issue 7 (2nd July 2020) - Coundouriotis, Eleni
ABSTRACT: This article offers a reading of Guantánamo Diary that aims at decentring left critiques of the war on terror by offering a postcolonial perspective of Mohamedou Ould Slahi's important testimony of forced disappearance and torture. The analysis is an exploration of textuality in Guantánamo Diary that takes up three questions in turn: what is the impact of writing an account of torture on our understanding of the literary? What are the stakes of postcoloniality in this text, especially in the context of human rights' appearance as colonial mimicry in Slahi's account? And finally, how does the emphasis in this reading of Guantánamo Diary on textuality and postcoloniality together reframe the robust critiques by US intellectuals of the war on terror, especially Judith Butler's reflections on indefinite detention?